Bacteriology of Antral Effluents and their Sensitivities at IKOT EKPENE and Calabar, South-South Nigeria. - Mgbe, DR Robert B; Offiong, Dr Mbora E.; Adekanye, Dr Abiola Grace; Emanghe, Dr Ubleni (British Journal of Healthcare and Medical Research, 2020)
Sinusitis is a common infection all over the world. It occurs very often together with rhinitis and the term rhinosinusitis is used interchangeably with sinusitis. It is usually triggered by viral inflammation of the sinuses which is later followed by bacterial infection, Objective: The aim of this study is to find out the microbial distribution in antral sinus effluents in calabar and Ikot ekpene and to determine their sensitivity pattern. Method: Patients with symptoms like headache, cacosmia, purulent nasal discharge and confirmed radiological evidence of sinusitis had antral washout done on one or both sides. The effluent was collected and immediately sent to the microbiology lab for microscopy, culture and sensitivity. Results: Forty eight patients were used for the study during a nineteen year period; year 2000- 2019.There were 30 males and 18 females with a male:female ratio of 1.6:1. The age range was 10-70 years with a mean age of 40 years. The distribution of microbes seen was as follows; Staphylococcus species(29.1%), Streptococcus species(18.7%), Coliforms (16.7%), Heamophilus, Proteus, Bramharella and Pseudomanas (4.2%) each, Candida (2.0%) and no growth in(16.7%). Ofloxacin, ciprofloxacin, genticin, ceftriaxone and augmentin had good sensitivity to the microbes while chloramphenicol and ampicillin had very low sensitivity. Conclusion: Rhinosinusitis occurs more in adults. Staphylococcus streptococcus and coliforms are the dominant species in our environment. Ofloxacin, ciprofloxacin, ceftriaxone and augmentin are the antibiotics with the highest sensitivity.